THE DESULFURIZATION OF DIESEL FUEL USING NATURAL ZEOLITE ADSORBENT - Anda Lusia (Jurnal Zeolit Indonesia, 2009)
Common way has been done to reduce sulfur in fuels is by conventional techniques of hydro desulphurization (HDS), which needs high investment to reduce sulfur bounded as aromatic organosulphur. The alternative technologies of sulfur reduction is using a zeolite absorbent are promising due to ambient operating condition and simple technology. The experiment of sulfur reduction conducted by batch with temperatures around 25oC and contact time around 2 hours with stirring magnetic stirrer speed 100 RPM and addition some of weight zeolites into 100 mL of diesel fuels. Application of natural zeolite Lampung and Malang in experiment of sulfur reduction at diesel fuel with addition 1 g showed that sorption capacity (q) of zeolite Malang (0,58-0.60) larger than Zeolite Lampung (7,17) which is equally to sulfur reduction (h) of zeolite Malang (i.e. 7,17) in which larger than that of zeolite lampung (i.e. 1,48%). The desulphurization treatment using Ni metal ion addition into zeolite shown the increasing of sorption capacity of Ni-Zeolite toward the decreasing of sulphur in diesel fuels. The highest improvement capacity of sorption occurred on zeolite Malang with addition 0.5 g Ni-zeolite that is 1.72.